Loneliness and fearfulness are associated with non-fatal drug overdose among people who inject drugs. - Oluwaseun Falade-Nwulia; Kathleen Ward; Karla D Wagner; Hamidreza Karimi-Sari; Jeffrey Hsu; Mark Sulkowski; Carl Latkin; Evaristus Nwulia (PLoS ONE, 2024)
Background People who inject drugs (PWID) experience high rates of drug overdose death with the risk of mortality increasing after each non-fatal event. Racial differences exist in drug overdose rates, with higher rates among Black people who use drugs. Psychological factors may predict drug overdose. Methods Cross-sectional data from a survey administered to PWID in Baltimore, MD enrolled in a social network-based intervention were analyzed. Linear regression methods with generalized estimating equations were used to analyze data from indexes and network members to assess for psychological factors significantly associated with self-reported number of lifetime drug overdoses. Factors associated with number of overdoses were assessed separately by race. Results Among 111 PWID enrolled between January 2018 and January 2019, 25.2% were female, 65.7% were Black, 98.2% reported use of substances in addition to opioids, and the mean age was 49.0 ± 8.3 years. Seventy-five individuals (67.6%) had a history of any overdose with a mean of 5.0 ± 9.7 lifetime overdoses reported. Reports of feeling fearful (β = 9.74, P = 0.001) or feeling lonely all of the time (β = 5.62, P = 0.033) were independently associated with number of drug overdoses. In analyses disaggregated by race, only the most severe degree of fearfulness or loneliness was associated with overdose among Black participants, whereas among White participants, any degree of fearfulness or loneliness was associated with overdose. Conclusions In this study of PWID loneliness and fearfulness were significantly related to the number of reported overdose events. These factors could be targeted in future interventions.